2000
DOI: 10.1021/jm000156+
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Additional Hydrophobic Binding Site, the Z Site, in the Rational Drug Design of a New Class of Stronger Trypanothione Reductase Inhibitor, Quaternary Alkylammonium Phenothiazines

Abstract: Improved rationally designed lead drug structures against African trypanosomiasis, Chagas disease, and leishmaniasis were obtained against trypanothione reductase from Trypanosoma cruzi. Substituted-benzyl [3-(2-chloro-4a, 10a-dihydrophenothiazin-10-yl)propyl]dimethylammonium salts, synthesized by Menschutkin quaternization of the tertiary alkylamine omega-nitrogen atom of chlorpromazine, were linear, competitive inhibitors of recombinant trypanothione reductase from T. cruzi, with either trypanothione disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 41 publications
7
108
0
8
Order By: Relevance
“…Most of them include nitrogen heterocycle rings such as quinolines 9 , quinazolines 10 , acridines 11 , pyrimidines 12 , pyrazols 13 , pyridines 8 , benzothiazoles 14 , imidazoles 15 , thiadiazoles 16 and include functional structures such as alkyl phospholipids 17 , ether phospholipids 18 , chalcones 19 , amidines 20 , oximes 21 , amidoxime 22 , hydrazones 23 and hydrazides 24,25 . On the other hand, a number of quaternized amine derivatives such as thiadiazolium-phenylamine 26,27 , arylisoquinolinium 28 , imidazo-pyridinium 29 , alkylammonium-phenothiazines 30 , indolo-quinolinium 31 and naphthalimide-amonnium 32 were previously reported to exert antiprotozoal properties. Antiprotozoal activity of quaternary ammonium compounds against Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them include nitrogen heterocycle rings such as quinolines 9 , quinazolines 10 , acridines 11 , pyrimidines 12 , pyrazols 13 , pyridines 8 , benzothiazoles 14 , imidazoles 15 , thiadiazoles 16 and include functional structures such as alkyl phospholipids 17 , ether phospholipids 18 , chalcones 19 , amidines 20 , oximes 21 , amidoxime 22 , hydrazones 23 and hydrazides 24,25 . On the other hand, a number of quaternized amine derivatives such as thiadiazolium-phenylamine 26,27 , arylisoquinolinium 28 , imidazo-pyridinium 29 , alkylammonium-phenothiazines 30 , indolo-quinolinium 31 and naphthalimide-amonnium 32 were previously reported to exert antiprotozoal properties. Antiprotozoal activity of quaternary ammonium compounds against Acanthamoeba spp.…”
Section: Introductionmentioning
confidence: 99%
“…A number of groups have reported on the successful design of inhibitors directed against trypanosomal (2,4,(15)(16), leishmanial (6), malarial (19), and tritrichomonal (3, 27) targets active in the 10 nM to 50 M range. However, with the number of compounds that could be generated by combinatorial chemistry growing exponentially, it has become apparent that chemical diversity has surpassed the capacity of high-throughput screening.…”
mentioning
confidence: 99%
“…Although potent inhibitors of TR could be developed by means of molecular modeling and quantitative docking techniques (22), it was found that several different modes of binding of such compounds to TR are energetically allowed. The authors conclude that with inhibitors not docked to a unique locus, it may be difficult to obtain good X-ray diffraction data for their binding to TR.…”
Section: Inhibitors Of Trypanothione Metabolismmentioning
confidence: 99%